ANALISIS EFEKTIVITAS DAN EFISIENSI PENGELOLAAN MODAL KERJA PADA PT. PLN (PERSERO) CABANG KUPANG - Yuri Sandra Fa’ah (Journal of Management Small and Medium Enterprises (SMEs), 2017)
This research aims to investigate the effectiveness and efficiency of the management of working capital atPT. PLN (Persero) Branch Kupang Area of East Nusa Tenggara. This study will provide the input to PT.PLN (Persero) Area Branch Kupang of East Nusa Tenggara to increase the effectiveness and efficiency ofthe management of working capital and to contribute for academics references. The data types arequalitative and quantitative, sourced from primary data and secondary data. Data collection techniquesare documentation and interviews. Methods of analysis is Financial Ratios Analysis i.e., Liquidity Ratio,Activities Ratio and Profitability Ratio and the Analysis of the Sources and the usages of Working Capital.The Liquidity Ratio is focused on Current Ratio, Quick Ratio and Cash Ratio; Activity Ratio is focused onReceivable Turnover, Inventory Turnover, Working Capital Turnover and Cash Turnover. ProfitabilityRatio prioritized on Net Profit Margin, Turnover of Operating Assets and Return on Investement. Theresults showed that, Financial Ratio indicated that in the aspect of liquidity PT. PLN (Persero) East NusaTenggara Region Branch was not found any problem overally, however, the aspect of Cash Availabilitywas not enough to finance the due debt immediately, the Average Rate of Turnover Assets relatively slowthat showed by the less of Assets Optimalization, and the tendency of profit rising achievement is smallerthan the using of existing Fixed Assets. It was recommended to improve the effectiveness and efficiency ofthe management of Working Capital which included Working Capital Controlling, Receivables TurnoverControlling, Expansion of the Area of Marketing and Increaeing of Working Capital.Keywords : Working Capital, Financial Ratios Analysis, Liquidity Ratio, Liquidity Ratio, ProfitabilityRatio